OPTIMIZING REGIONAL HOSPITAL SERVICES THROUGH ORGANIZATIONAL LEARNING WITH LIMITED RESOURCES - Almansyah Rundu Wonua; Ismanto Ismanto; Ansar Abbas; Sudarnice Sudarnice; Fauzih Fauzih (Universitas Sains Al Qur'an, 2026)
Hospitals are essential in delivering healthcare services to the public, In providing quality services, hospitals are faced with challenges such as limited facilities, budgets, medical personnel, and the emergence of various ever-changing government regulations that force hospitals to follow these rules. Facing various challenges in providing quality health services, hospitals need to adopt organizational learning. Organizational learning allows hospitals to adapt, innovate, and optimize their limited resources. This Study aims to analyze the factors that affect organizational learning in order to improve public services in regional hospitals with limited resources. This research uses a quantitative approach with a survey method and data analysis using Structural Equation Modeling (SEM)-PLS with Smart PLS 3.0. The results of this study indicate that organizational culture and psychological climate are strategies to overcome the limitations of organizational resources and can support effective organizational learning for hospitals. This is due to an organizational culture that supports collaboration among individuals to exchange knowledge and experience to solve the challenges they face in the condition of limited resources, limited facilities, budgets, and medical personnel. The research contribution shows that organizational learning in regional hospitals is often hampered by several factors, but with organizational Culture consistently is one of the main determining facts of organizational learning. This study has limitations because it was conducted at a single hospital, Konawe Regional Hospital, so the results are limited in their generalizability to other organizations or sectors. Furthermore, this study focused solely on organizational culture and psychological climate variables in explaining organizational learning, so there is the possibility that other unexamined variables may also be influential, such as leadership style, absorptive capacity, knowledge management, or knowledge-sharing practices.